Determination of the level of tactical readiness of qualified runners at 800 m - Tetiana Rybalchenko; Olena Nasonkina; Mykhailo Marchenkov (Kharkiv State Academy of Physical Culture, 2018)
Purpose: determine the change in the level of tactical preparedness and tactics of competitive activity of qualified runners at 800 m. Material & Methods: theoretical analysis and generalization of literary sources; pedagogical observation; analysis of competitive activities; method of expert evaluation; methods of mathematical statistics. To determine the level of tactical preparedness of the runners, 20 experts were involved (10 coaches and 10 highly qualified athletes). The study involved athletes I category and CMS, specializing in running at 800 m aged 17-21 (10 boys and 10 girls). Results: revealed a low level of tactical preparedness of runners at 800 m. Improved tactical readiness indicators, namely the ability to analyze information about their rivals and the ability to use it during competitions, increase the diversity of the arsenal of tactical actions, increase the ability to impose their tactics and ability to quickly respond to the situation, which has changed, and instantly change tactical techniques depending on the opponent's behavior. Conclusion: shows the positive effect of specially designed exercises on the level of tactical preparedness of athletes. The redistribution of efforts of athletes at a distance, an increase in the average competitive speed and sports result.